The DEVELOPMENT OF TEACHING MATERIALS BASED ON MIXED-REALITY TECHNOLOGY TO IMPROVE COMPUTER ASSEMBLY COMPETENCE OF SMK STUDENTS - Suryadi, Ahmad; Sadat, Anwar (Jurnal Pendidikan Indonesia, 2025)
The lack of Mixed-Reality (MR)-based teaching materials developed for vocational high school students is an obstacle in supporting their readiness to face the challenges of Industry 4.0. This study aims to design of Mixed-Reality (MR) technology-based instructional materials to enhance students' computer assembly competencies. The research method employed is research and development (R&D) using the Four-D model (Define, Design, Develop, Disseminate). The research subjects consisted of one teacher and 32 tenth-grade students as test subjects. Data were collected through validation questionnaires (media, materials, and instructional design), pretest and posttest, and student response questionnaires. Research instruments included expert validation sheets, multiple-choice test questions, and student attitude questionnaires. Data analysis techniques used quantitative descriptive analysis and gain scores to measure competency improvement. The research results indicate that MR-based instructional materials are highly feasible, with an average validation score of 3.51. Their application in learning significantly improved students' computer assembly competencies, with an average increase of 13.5 points and 61.1% of students achieving moderate to high gain scores. The conclusion of this study is that MR-based instructional materials are proven to be effective and feasible for enhancing vocational high school students' practical competencies. The implications of this study highlight the importance of integrating immersive technology into vocational education as an effort to bridge the gap between theory and practice and equip students with 21st-century skills.